Audit Delay in the Islamic Capital Market: The Moderating Power of Auditor Reputation on Risk and Complexity (ISSI 2021–2024) - Dewi Astuti; Nur Kabib (Center for Indonesian Accounting Studies, 2026)
Research Objective - This study examines the effects of leverage, firm size, and business diversification on audit delay, with the Public Accounting Firm's reputation as a moderator, among consumer goods companies listed on the Indonesian Sharia Stock Index (ISSI) during the 2021–2024 period.Method - This study employs a quantitative, panel-data approach. Data analysis was conducted using panel regressiondata assistance in EViews.Findings - The results indicate that leverage has a positive and significant effect on audit delay. Firm size has a negative and significant effect on audit delay. Business diversification does not have a significant effect on audit delay. Furthermore, the reputation of the Public Accounting Firm does not moderate the relationship between leverage and audit delay; however, it moderates the relationships between firm size and audit delay and between business diversification and audit delay.Theoretical and Policy Implications - The findings reinforce agency theory by showing that firm characteristics and auditor quality play an important role in audit delay. Therefore, management should enhance transparency and strengthen internal controls to minimize audit delays. In addition, regulators and capital market authorities are encouraged to strengthen supervision and promote higher audit quality to ensure the timeliness of financial reporting among Sharia-listed companies.Research Novelty - This study offers novelty by examining audit delay from an agency theory perspective among consumer goods companies listed on the ISSI during the 2021–2024 period. In addition, this study incorporates business diversification as an explanatory variable and measures the reputation of Public Accounting Firms using a three-level ordinal scale, providing a more comprehensive measure than the dummy variable approach commonly used in prior studies.